Semi-Automated Assessment of Long-Term Olfactory Habituation in Drosophila melanogaster Using the Olfactory Arena - Camilla Roselli; Mani Ramaswami; Marcia Aranha (Bio-Protocol)
Long-lasting memories are a core aspect of an animal’s life. Such memories are characterized by unique molecular mechanisms and often unique circuitry, neither of which are completely understood in vivo. The deep knowledge of the identity and connectivity of neurons of the fruit fly Drosophila melanogaster, as well as the sophisticated genetic tools that allow in vivo perturbations and physiology monitoring, make it a remarkably useful organism in which to investigate the molecular mechanisms of long-term memories. In this protocol, we focus on habituation, a non-associative form of learning, and describe a reliable, semi-automated technique to induce and assess long-term olfactory habituation (LTH) in Drosophila using the olfactory arena, thus providing a method aligned with recent technological progress in behavioral measurement. Prior work has shown that LTH is induced by a 4-day exposure to an odorant and is characterized by a long-lasting (> 24 h) reduction in behavioral response to the exposed odorant, measured using a manual and skill-intensive Y-maze assay. Here, we present a semi-automated protocol for obtaining quantifiable measures of LTH, at the level of detail required for other investigators in the field. Unlike previously described methods, the protocol presented here provides quantitative and detailed behavioral measurements obtained by video recording that can be shared with the scientific community and allows sophisticated forms of offline analysis. We suggest that this procedure has the potential to advance our understanding of molecular and circuit mechanisms of olfactory habituation, its control via neuromodulation, and its interactions with other forms of memory.